Influence of citric acid and curing time on water uptake - Izhar, S.M.M. (Trans Tech Publications Ltd, 2014)
Starch is highly promising biopolymer for the production of packaging material since it gives films a good tensile and gas barrier properties. However, non-plasticized starch films are brittle and their hydrophilic character results in poor moisture barrier properties and high water sensitivity. In order to improve films formation and material properties of starch, plasticization and chemical modification such as cross-linking of the starch is required. The cross-linking reaction able to improve thermal stability, tensile strength and decreased the dissolution of starch films in water and formic acid. From the study, the percentage of water uptake reduced when the blending ratio of citric acid increased. The percentage of water uptake highly affected by curing time compared to blending ratio. Increasing the curing time from 1 hour to 2 hour significantly reduced the percentage of water uptake. At 4 hour curing time, the percentage water uptake reached equilibrium faster than 3 hour curing time. This shows that more citric acid molecules were chemically bonded with the starch chains, resulting in higher cross link degree and thus, reduced the percentage of water uptake. Â© 2014 Trans Tech Publications, Switzerland.